The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2174/1871520618666180412120128
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Pomolic Acid in Acute Myeloid Leukemia Cells Involves Cell Death, Decreased Cell Growth and Topoisomerases Inhibition

Abstract: Finally, this study showed that PA has powerful antitumor activity against AML cells suggesting that this natural compound might be a potent antineoplastic agent to improve the treatment scheme of this neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, PA down-modulated MRP1/ABCC1 activity in both PC3 and PC3R cell lines, thus suggesting that this mechanism is responsible for PA’s cytotoxicity observed in both cell lines [ 225 ]. In acute myeloid leukemia cell lines HL60, U937, and Kasumi-1, PA decreased cell viability and cell growth and induced cell death via the activation of the caspase pathway and inhibition of hTopo I and IIα human DNA topoisomerases in all cell lines [ 10 ].…”
Section: Pomolic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PA down-modulated MRP1/ABCC1 activity in both PC3 and PC3R cell lines, thus suggesting that this mechanism is responsible for PA’s cytotoxicity observed in both cell lines [ 225 ]. In acute myeloid leukemia cell lines HL60, U937, and Kasumi-1, PA decreased cell viability and cell growth and induced cell death via the activation of the caspase pathway and inhibition of hTopo I and IIα human DNA topoisomerases in all cell lines [ 10 ].…”
Section: Pomolic Acidmentioning
confidence: 99%
“…Triterpenes are well-represented phytocompounds with over 30,000 representants [ 7 ] that have received increased attention as a result of various biological properties, including anticancer, anti-inflammatory, hepatoprotective, antiviral, cardioprotective, and antimicrobial effects [ 8 ]. Among them, some triterpenic acids have been found to exert selective antiproliferative effects triggered mainly by apoptotic-dependent mechanisms [ 9 , 10 , 11 , 12 ]. Despite their remarkable properties, their lipophilic core imprints unfavorable physical-chemical properties that greatly hamper their bioavailability and consequent development as therapeutic drugs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously isolated many compounds from the flowers of A. satureioides , including triterpenics, anthraquinones, and flavonoids. Research has shown that pomolic acid (PA) and its glucopyranose ester have effects against breast cancer[ 8 - 10 ], prostate cancer[ 11 ], leukemia[ 12 - 15 ], and other malignant tumors. Because of its high safety, these agents have been increasingly used in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%